PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH MELALUI PROGRAM “TUKA TUKU” OLEH DINAS KOPERASI USAHA KECIL DAN MENENGAH DI KABUPATEN PUBALINGGA - Nur Fadhila, Aisyah; Maesaroh, Maesaroh; Puspo Priyadi, Budi (Journal of Public Policy and Management Review, 2024)
The percentage of Purbalingga's Gross Regional Domestic Product (GRDP) by business field shows that the processing industry sector is the largest contributor with a contribution of 27.24%. Seeing the large role of MSMEs in the economy of Purbalingga Regency, this sector has great potential for further empowerment and development. One of the efforts made by the Purbalingga Regency Government through the Small and Medium Enterprises Cooperative Office is to establish a program or platform for MSMEs to improve the promotion and marketing of their products, known as “Tuka Tuku”. This program is regulated in Purbalingga Regent Regulation Number 71 of 2019 concerning “Tuka Tuku” Purbalingga Products. This study aims to analyze the form of MSME empowerment through the “Tuka Tuku” program implemented by the Office of Cooperatives, Small and Medium Enterprises in Purbalingga Regency. The research method used is qualitative with interviews, where informants are selected using purposive sampling. The results showed that this program focuses on training and coaching services, socio-economic empowerment of the community by providing knowledge about product packaging, licensing, and marketing strategies. In addition, the Tuka Tuku program also strengthens institutions by encouraging the formation of Joint Business Groups (KUB) and collaboration with non-governmental institutions so as to create an ecosystem that supports MSMEs. However, there are several challenges in empowering MSMEs in Purbalingga Regency. Internal constraints include difficulties in managing raw material supply, lengthy processes in obtaining packaging materials, as well as production and delivery logistics issues. External challenges include unpredictable market dynamics, as well as varying levels of success in marketing MSME products through this program.